Scholarship Information Service on UIN Ar-Raniry Banda Aceh Website - Muhammad Akbar; Anita; Hanifah (Winaya Inspirasi Nusantara Foundation, 2023)
This study aims to determine how information disclosure and scholarship information service updates on the UIN Ar-Raniry Banda Aceh website. The method used in this study is descriptive-qualitative. Data collection techniques include observation, interviews, and documentation. The object of research is the official website manager of UIN Ar-Raniry Banda Aceh, the student and alumni administration and student development section, and some of the students of UIN Ar-Raniry Banda Aceh. The results showed that the openness of scholarship information provided by UIN Ar-Raniry Banda Aceh to students is not open because on the scholarship website submenu there is no regular scholarship information update. And the update of scholarship information services on the UIN Ar-Raniry website provided to students on the scholarship submenu website does not have information services as a scholarship information website because information is not updated regularly. This is influenced by the lack of human resources (HR) managing the UIN Ar-Raniry Banda Aceh website.